Komunikasi dan Partisipasi Perempuan Dalam Politik Elektoral - Setiawati, Titin; Agustini, Vilya Dwi (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This research aims to investigate the background of women's participation in general and specifically, women who participate in electoral politics as legislative candidates. Using phenomenological methods, the study states that the backgrounds of women who are involved in electoral politics include following in the footsteps of other people who have already entered the world of politics, wanting women to play more roles, and being encouraged by other people. The participation of women in politics still mostly comes from external sources, rather than being purely driven by a desire to change women's conditions due to patriarchal relations in society. Meanwhile, the most common obstacles experienced by women in politics are the double burden of having to play both domestic and public roles, social and cultural inequality, and being underestimated as women. Regarding the communication strategy used by female legislative candidates, they stated that they communicate more with female prospective voters, explain programs related to women, children, and teenagers, and discuss issues related to women to attract votes. They believe that gender similarity helps them communicate effectively and achieve their political goals.